The Effect of Budget Transparency on Public Trust in the Regional Planning, Research, and Development Agency of North Central Timor Regency - Eduard Sandhyko Nitsae; Detson Ray Halomoan Sitorus; Marthen Patiung; Aplonia Pala (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2026)
This study was conducted to examine the impact of budget transparency on public trust in the Public Accountability Agency for Planning, Research, and Innovation (BAPPERIDA) of North Central Timor Regency. Budget transparency is a cornerstone of good governance principles, emphasizing information openness, accountability, and public participation in development planning and financial management. In this context, public trust is crucial for the legitimacy, effectiveness, and success of local government administration. The background of this study is based on the fact that public access to budget information remains limited, and the level of public involvement in local budget planning and oversight is low. Although BAPPERIDA’s annual budget execution rate is relatively high, information transparency toward the public remains suboptimal, leading to low public trust. This study is quantitative in nature and employs an explanatory research design. Questionnaires were distributed to 96 BAPPERIDA members, and data were collected. After conducting validity and reliability tests on the instruments, data analysis was performed using simple linear regression with SPSS. Budget transparency, assessed based on the indicators of informativeness, openness, and disclosure of information, is closely related to public trust, which is measured through commitment, sincerity, honesty, competence, and fairness. The research findings indicate a positive and significant relationship between budget transparency and public trust, with a regression coefficient of 0.636 and a significance level of 0.000 (<0.05). This indicates that increased implementation of budget transparency will enhance public trust in BAPPERIDA. Therefore, budget transparency is a crucial element in fostering accountable, credible, and trustworthy local governance.